Analysis of Karate Athlete Physical Condition Test Results on PPLP Athletes of Gorontalo Province In 2022 And 2023 - Nurkhoiroh; Haryani, Meri; Isnanto, Juni; Irawan, Safri; Barus, Jan Bobby Nesra Barus (Universitas PGRI Palembang, 2024)
The recommendation of this research is to obtain differences in the results of physical condition tests that focus on kata number karate and kumite athletes from PPLP Gorontalo Province and to find out the percentage of physical condition test participants from kata number karate and kumite athletes from PPLP Gorontalo Province athletes. Apart from that, this research is an evaluation of the results of the number kata and kumite karate tests every year from 2022 to 2023. This research shows the results of the physical tests on kata number karate and kumite of female PPLP athletes from Gorontalo province in 2022 - 2023 PPLP Gorontalo Province, namely Test The 20 meter run in 2022 - 2023 experienced an average increase of 0,33%, the Bleep test in 2022-2023 experienced an average increase of 0,49%. the 300m running test in 2022-2023 experienced an average increase of 11,70%, the Sit up test in 2022 – 2023 experienced an average increase of 19,75%, the Push up test in 2022 – 2023 experienced an average increase of 125 .64%. Meanwhile, the results of the physical tests for karate athletes, kata numbers and kumite for PPLP male athletes in Gorontalo Province for 2022 - 2023 PPLP Gorontalo Province, namely the 20 meter running test from 2022 to 2023, experienced an increase of 2,62% on average, Bleep test in 2022-2023 will experience an average increase of 205,62%. the 300m running test in 2022-2023 experienced an average increase of 8,04%, the Sit up test in 2022-2023 experienced an average increase of 26.40%, the Push up test in 2022 –2023 experienced an average increase of 205 ,62%.So there will be changes in the physical condition test results of Gorontalo Province PPLP from Gorontalo Province PPLP in 2022 - 2023. The most prominent changes in test results are in the results of the 20m run test, bleep test, 300m run, Sit-ups and Push-ups.